Fantasy Worlds on the Small Screen: Worldbuilding in Original American Fantasy Television. Issue 1 (1st March 2021) - O'Dette, Katarina
Abstract : This article draws on worldbuilding theory, US television industrial practices, and textual analysis of a variety of fantasy series to explore the medium-specific forces that shape how fantasy worlds are built on television. With particular focus on Buffy the Vampire Slayer (1997–2003), Once Upon a Time (2011–2018), and Dead Like Me (2003–2004), this article proposes the concepts of stationary movement and adaptive creation to analyze how televisual worldbuilding is shaped by industrial practices such as standing sets and actors' contracts. Scrutinizing the medium-specific manifestation of fantasy worlds on television, this article aims to address the gap in the literature surrounding this televisual genre.